How to develop Capacity Building among the Teacher‟s - Raju , S.Ch. (Educational Trend (A Journal of RIE, Ajmer - NCERT), 2025)
As new learning Skills emerge its necessary for Education System to respond to make sure teacher‟s have sufficient capacity to develop learning programs that will provide the opportunity for students to develop these new learning skills. “A capacity building approach, through formal and informal professional learning experience, to ensure teachers develop competencies and capacity to help improve learning out comes and prepare students for the rapidly changing world of work. Capacity Building or development is the process by which individuals, groups, organizations institutions, societies and subject resource persons increase their abilities to perform core functions, solve problems, define and achieve objectives, capacity building can be described as a sustainable process of equipping teachers with the knowledge, skills and attitudes to enable them to cope with change and achieve the desired educational out comes. For the education sector, capacity building can be divided in to individual, group, school and system target groups. Each group is strongly interrelated in this scenario; capacity building can be defined as follows.